Single atrium - a rare case report - Kalita, Jyoti Prasad; Saikia, Manuj Kumar; Sharma, Amitav; Saikia, Biswajeet; Das, Gautam Chandra (International Journal of Research in Medical Sciences, 2017)
Single atrium is a rare congenital heart disease in which there is developmental absence of both septum primum and secondum part of atrial septum. Present study reports a case of an adolescent female patient with single atrium without any endocardial cushion defect and other variety of congenital heart disease. Clinically the patient presented with features of congestive heart failure. She underwent successful surgical separation of atrium.